The NH2-Terminal Ig Domains of Insect Projectin could serve as Elastic Elements - Agnes Ayme-Southgate; Mary Crowe; Richard Southgate (Journal of Proteomics and Genomics Research, 2012)
The connecting C-filaments of insect indirect flight muscles have been proposed as one of the elements providing muscle elasticity for the asynchronous muscle physiology of derived insects. Two large modular proteins, kettin/Sallimus and projectin make up these filaments, and for both proteins the N-terminal sequences span the extensible I-band and are proposed as the elastic segments. The C-filaments have not been studied in insects, such as dragonflies, crickets, and Lepidoptera with muscles which are largely synchronous in physiology and display different levels of muscle stiffness. In this paper we focus our efforts on the projectin protein of several insects with synchronous flight muscles; namely dragonfly, cricket, and moth. We provide evidence for the localization of projectin over the sarcomere I-Z-I region that is consistent with the existence of C-filaments in synchronous flight muscles. Additionally, we determine the sequences for the NH2-terminal region of projectin in these insects and describe the presence of alternative splice variants. Using predictors of intrinsically disordered regions, we identify possible unfolded segments, especially around the short linker sequences found between the NH2 Ig domains. We propose a possible picture of projectin NH2-terminal region organized as different segments contributing elastic responses to stretch by either unfolding of highly disordered sequences (PEVK) or reorientation of domains by bending or twisting of disordered linkers between the Ig domains.
Keywords: insect